Social Contracts as Assets: A Possible Solution to the Time-Consistency Problem - Kotlikoff, Laurence J.; Persson, Torsten; Lars E. O. Svensson (American Economic Review, 1988)
[We present a new solution to the time-consistency problem that appears capable of enforcing ex ante policy in settings where other enforcement mechanisms do not work. The solution involves a social contract that specifies the optimal ex ante policy and is effectively sold by successive old generations to successive young generations, who pay for the social contract through intergenerational transfers. Both old and young generations have an economic incentive to fulfill the social contract.]